Race and ethnicity in the 21st century - Bloch, Alice, 1964-; Solomos, John. (Houndmills, Basingstoke, Hampshire : New York, NY : Palgrave Macmillan, 2010)
"The 21st Century has seen important changes in the role of race and ethnicity. Exploring original research, empirical data and theory, this book examines major questions and issues around housing, employment, asylum, crime and health. Written by experts in the field, the text gives students of sociology useful insight into race and ethnicity today"--Provided by publisher.
Key questions in the sociology of race and ethnicity / A.Bloch & J.Solomos -- Housing and neighbourhoods: A UK and European perspective / M.Harrison & D.Phillips -- New communities: Asylum seekers and dispersal / P.Hynes & R.Sales -- The continuing significance of "race": Racism, contentious antiracist politics and labour markets / S.Virdee -- Community cohesion and national security : rethinking policing and race / E.McLaughlin -- Health and Health Care / J.Nazroo -- Education / D.Gillborn & N.Rollock -- Media representations of diversity: The power of the mediated image / M.Georgiou -- Identity and Public Opinion / A.Heath, C. Rothon, & S. Ali -- Race and ethnicity in Britain: Into the 21st Century; A.Bloch & J.Solomos.
Includes bibliographical references and index.
Keywords: Race relations -- History -- 21st century; Ethnic relations -- History -- 21st century; Multiculturalism -- History -- 21st century